Building geospatial competences in Tanzanian universities with open source solutions - Käyhkö N.; William C.; Mayunga J.; Makame M.; Mauya E.; Järvi A. (Germany, 2022)
The GEO-ICT is an institutional cooperation project aiming at improving the quality and societal relevance of geospatial and ICT research and education at the Universities of Dar es Salaam (UDSM), Ardhi University (ARU), State University of Zanzibar (SUZA) and Sokoine University of Agriculture (SUA). Jointly with the University of Turku (UTU) Finland, the institutions focus on strengthening geospatial and ICT skills of the staff, establishing new curricula, upgrading supportive infrastructures and creating synergetic cooperation modalities with different stakeholders in the society. In this paper we share how our practical experiences of the cooperation, including what is the background for the establishment of institutional cooperation between these universities, how is the project operating in practice, what type of activities and cooperation modalities we do together and how do we think institutional cooperation contributes to the advancement of geospatial expertise in Tanzania and what is the role of open source solutions in this development.
FOSS4G 2018